2018
DOI: 10.1371/journal.pone.0193396
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term outcome of smear-positive tuberculosis patients after initiation and completion of treatment: A ten-year retrospective cohort study

Abstract: BackgroundThe status of tuberculosis (TB) patients since initiation of treatment is unknown in South Ethiopia. The objective of this study was to assess the long-term outcomes of smear-positive TB patients since initiation and completion of treatment, which includes TB recurrence and mortality of TB patients.MethodsWe did a retrospective cohort study on 2,272 smear-positive TB patients who initiated treatment for TB from September 1, 2002—October 10, 2012 in health facilities in Dale district and Yirgalem town… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Dangisso et al revealed that people over the age of 34 were twice as likely to die from TB. [28] These results are similar to those of our study, in which the median age was 34 years. This may be due to the increase of comorbidities with age as it was reported in that Ethiopian study.…”
Section: Discussionsupporting
confidence: 91%
“…Dangisso et al revealed that people over the age of 34 were twice as likely to die from TB. [28] These results are similar to those of our study, in which the median age was 34 years. This may be due to the increase of comorbidities with age as it was reported in that Ethiopian study.…”
Section: Discussionsupporting
confidence: 91%
“…In this setting, presumptive TB cases were continuously identified and screened through a house-to-house visit for two years prior to the survey by innovative community based approach by TB REACH project [ 19 ]. The low prevalence reported from this district could be a proxy to declining in prevalence or lower TB incidence due to the intervention and long term implementation of DOTS [ 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a ten-year retrospective cohort study, consisting of 2730 smear-positive TB cases, 458 (16%) eligible TB cases were missed from a survey due to migration to other areas. 27 Some of these cases might have migrated to low TB incidence areas or to receiving countries which may have their TB epidemiology affected. Various studies reported that people with history of TB treatment may have recurrent TB.…”
Section: Migration and Tbmentioning
confidence: 99%
“…Various studies reported that people with history of TB treatment may have recurrent TB. 27 , 28 Generally, the incidence of TB is low in high-income countries, however, it is high among specific groups of people such as migrant populations. Migrants in low TB incidence countries may come from high TB burden areas, where they have contracted mycobacterium tuberculosis infections.…”
Section: Migration and Tbmentioning
confidence: 99%